Centralized vs. de-centralized multinationals and taxes - Søren Bo Nielsen; Pascalis Raimondos-Møller; Guttorm Schjelderup (Center for Economic Studies and ifo Institute (CESifo), 2005)
The paper examines how country tax differences affect a multinational enterprise's choice to centralize or de-centralize its decision structure. Within a simple model that emphasizes the multiple conflicting roles of transfer prices in MNEs - here, as a strategic pre-commitment device and a tax manipulation instrument -, we show that (de-)centralized decisions are more profitable when tax differentials are (small) large.
Keywords: F23; H25; L23; 330; centralized vs. de-centralized decisions; taxes; MNEs; Multinationales Unternehmen; Steuer; Organisationsstruktur; Transferpreis; Theorie